2017
DOI: 10.3892/ol.2017.7426
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolaric acid B induced autophagy, but not apoptosis, in MRC5 human fibroblast cells

Abstract: Autophagy and apoptosis are closely associated. In previous studies, pseudolaric acid B (PAB), a diterpene acid isolated from the root and trunk bark of Pseudolarix kaempferi Gordon (Pinaceae), was demonstrated to induce apoptosis in various cell lines. However, in L929 murine fibrosarcoma and SW579 human thyroid squamous cell carcinoma cells, only autophagy was induced. In the present study, another cell line, MRC5 human lung fibroblast cells, was identified in which PAB only induced autophagy. The relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…PAB exhibits potent antitumor effects on human breast cancer MCF-7, cervical cancer HeLa and melanoma A375 cells by inducing apoptosis ( 1 5 ), and on murine fibrosarcoma L929, human thyroid squamous cell carcinoma SW579 cells and human lung fibroblasts MRC5 by inducing autophagy ( 6 8 ). In the present study, the effects of PAB were examined on human rhabdomyosarcoma RD cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PAB exhibits potent antitumor effects on human breast cancer MCF-7, cervical cancer HeLa and melanoma A375 cells by inducing apoptosis ( 1 5 ), and on murine fibrosarcoma L929, human thyroid squamous cell carcinoma SW579 cells and human lung fibroblasts MRC5 by inducing autophagy ( 6 8 ). In the present study, the effects of PAB were examined on human rhabdomyosarcoma RD cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescent compound MDC has been proposed as a tracer for autophagic vacuoles ( 6 8 ). RD cells (2×10 5 cells/well) were cultured in 6 wells plates for 24 h. 24 h later, RD cells were treated with 4 µM PAB for another 24 h and incubated with 0.05 mM MDC at 37°C for 1 h. Following incubation, the cells were washed once with PBS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, it was investigated that G2/M phase‐related drugs inhibited EVD68 production, it was found that pseudolaric acid B (Song et al, ; Wang et al, ), oridonin (Zheng et al, ), and erianin (Wang et al, ) did not affect intracellar viral protein expression although they had the trend to decrease the expression, therefore, it was speculated that the decreased trend was due to decreased viral mRNA level by pseudolaric acid B, oridonin, and erianin, respectively. Meanwhile, only oridonin affected supernatant viral protein expression, but all of them decreased supernatant viral genome level, and the fold difference in the TCID50/ml and the supernatant viral genome level between the control‐treated and pseudolaric acid B‐treated cells was 2.34 × 10 2 and 11.31, oridonin was 5.10 × 10 3 and 54.05, and erianin was 1.23 × 10 3 and 108.70, therefore, pseudolaric acid, oridonin, and erianin inhibiting viral genome packaged into virions partly explained the decreased production.…”
Section: Discussionmentioning
confidence: 99%